EFEKTIVITAS PENGGUNAAN MULTIMEDIA INTERAKTIF TERHADAP HASIL BELAJAR KOGNITIF PJOK SISWA SMP NEGERI 1 GALESONG UTARA - Eliana Putri; Rusli; Nurhikmah H; Suryadi Ishak; Safaruddin (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to determine the effectiveness of interactive multimedia in improving students’ cognitive learning outcomes in Physical Education, Sports, and Health (PJOK) at the junior high school level. The research employed a quasi-experimental method with a one-group pretest–posttest design involving 30 seventh-grade students from SMP Negeri 1 Galesong Utara. Students were given a pretest to measure their initial cognitive achievement, followed by learning activities using interactive multimedia, and finally a posttest to evaluate their learning improvement. The cognitive learning outcomes were measured using objective test instruments and analyzed using JASP software. The Shapiro–Wilk normality test showed that the data were normally distributed (p = 0.068). The paired samples t-test revealed a significant difference between pretest and posttest scores, with t = –14.55, df = 29, and p < 0.001. The mean score increased substantially from 55.67 in the pretest to 88.33 in the posttest. Furthermore, the effect size was very large (Cohen’s d = 2.656), indicating a strong impact of interactive multimedia on students’ cognitive learning outcomes. These findings confirm that interactive multimedia is highly effective in enhancing students’ understanding, engagement, and cognitive mastery in PJOK learning.